Etika Lingkungan dalam Perspektif Yusuf al-Qaradawy - Nahdi, Maizer Said; Ghufron, Aziz (Al-Jamiah Research Centre, Sunan Kalijaga State Islamic University, 2006)
Environmental crisis is in principal brought about by human activities. Therefore, it is required to exercise new approach towards the environment, that is ethical approach by which principles and moral guidance for human behaviors are put forward. This article is to describe Yusuf al-Qaraá¸Äwyâs thought of Islamic-ethical concept on environment, and its relevance with the handling of environmental-global crisis. His thought is based on Islamic jurisprudential and ethical values. Values of the former are the followings: planting barren land, keeping cleanliness, cultivation, and forestation, meanwhile those of the latter are the application of al-ihsÄn concept, being friendly with environment, destructive prohibition, justice, gratitude, and simplicity. Al-Qaraá¸Äwyâs concept is absolutely appropriate for the prevailing environmental-global crisis. It is hoped that Indonesian Muslims, as majority group, would like to comprehend the concept and to build consciousness of religious way of thinking towards the environment. Hopefully, this concept is workable for coping with the environmental crisis, as well.